2010
DOI: 10.13031/2013.34946
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Hydraulic Property Determination of Denitrifying Bioreactor Fill Media

Abstract: Denitrification bioreactors are one of the newest options for nitrate removal in agricultural drainage waters. Optimization of denitrification bioreactor design requires the ability to identify concrete values for the hydraulic properties of bioreactor fill media. Hydraulic properties, chiefly saturated hydraulic conductivity but also porosity and particle size, are not known for many types of possible bioreactor media though they have a significant impact upon bioreactor design and performance. This work was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 19 publications
4
38
0
1
Order By: Relevance
“…The results from this short-term study imply that woodchip media are capable of achieving higher nitrogen removal rates through higher flow rates. This confirms the findings of Christianson et al (2010), Cameron and Schipper (2012), Hoover et al (2016), and others and indicates the importance of optimization and proper evaluation of the effects of HRT when designing denitrifying woodchip bioreactors. The HRT should not be too long; otherwise, the nitrogen removal rate will decline.…”
Section: Nitrate-nitrogen Removal In Lab-scale Denitrification Bioreasupporting
confidence: 89%
See 1 more Smart Citation
“…The results from this short-term study imply that woodchip media are capable of achieving higher nitrogen removal rates through higher flow rates. This confirms the findings of Christianson et al (2010), Cameron and Schipper (2012), Hoover et al (2016), and others and indicates the importance of optimization and proper evaluation of the effects of HRT when designing denitrifying woodchip bioreactors. The HRT should not be too long; otherwise, the nitrogen removal rate will decline.…”
Section: Nitrate-nitrogen Removal In Lab-scale Denitrification Bioreasupporting
confidence: 89%
“…The woodchip porosity was determined using the standard porosity determination procedure described by Christianson et al (2010). The analysis revealed that the conifer woodchip porosity was 54%, the deciduous woodchip porosity was 53%, and the mixed woodchip porosity was 53%.…”
Section: Lab-scale Denitrifying Bioreactorsmentioning
confidence: 99%
“…Increased efficiency in terms of the percentage of regeneration and the number of produced shoot explants was observed on BM without growth regulators. This result can be explained with the presence of predetermined cells which first dedifferentiate themselves, subsequently form new meristematic centres, and finally differentiate again producing new organs [34][35][36][37][38][39]. This process, due to cell totipotency, has been observed in several species [30,[40][41][42][43][44][45][46][47] and is very efficient for regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Inflow and outflow flow manifolds consisted of perforated tile drainage pipes placed at the bottom of the bioreactor that were connected to the control structures with non-perforated tile pipe. The locally purchased hardwood chips were similar in size and shape to chips evaluated by Christianson et al (2010) (i.e., similar to chips the majority of which fell in the 9.5-25.4 mm particle size range) which had an average saturated hydraulic conductivity of 9.5 cm s −1 (Christianson et al, 2010). Like most drainage bioreactors in the Midwest, this reactor was designed and installed with a by-pass pipe to accommodate peak flow events.…”
Section: Site Descriptionmentioning
confidence: 99%
“…(1)). The porosity of 0.65 was developed from work by Christianson et al (2010) for similar woodchips. These previous methods estimated total porosity (i.e., including intraporosity, not just drainable porosity) by saturating woodchips for 24 h, adding additional water to account for woodchip water absorption over this period, and then using the total volume of water to calculate the porosity value.…”
Section: Site Descriptionmentioning
confidence: 99%